Study of the Reaction Rate of Gold Nanotube Synthesis from Sacrificial Silver Nanorods through the Galvanic Replacement Method. (11th July 2010) - Kwon, Sunil; Dong, Hyunbae; Lee, Sang-Yup
Abstract : An investigation was carried out about the gold nanotube synthesis via a galvanic replacement reaction. The progress of the gold nanotube synthesis was investigated using electron microscopy and UV-Vis spectroscopy. In addition, the reaction rates of gold nanotube formation in the early stage of the reaction were studied. The chlorine ion concentration linearly increased with the gold precursor concentration but deviated from the stoichiometric amounts. This deviation was probably due to AgCl precipitates formed by the reaction of chlorine ions with dissolved silver ions. The replacement reaction was promoted with increased temperature and was nonlinearly proportional to the gold ion concentration. The outcomes of this research will enhance the current understanding of the galvanic replacement reaction.